Strengthening and stabilization exercise in prevention of shoulder injuries - Bernarda Letnar (University of Banja Luka, Faculty of physical education and sport, 2020)
The shoulder joint is the most flexible joint in the human body which experiences high loads during certain sport activities involving overhead motion. Overhead athletes experience rapid shoulder elevation, abduction and external rotation during the movement and rapid deceleration after the movement, making them susceptible to shoulder injuries. Due to the extreme ranges of motion, overhead athletes tend to develop increased external rotation, combined with decreased range of internal rotation, emphasizing the need for balanced shoulder care program in the training process to prevent such occurrences. The aim of the research paper was to develop training regimen for injury prevention and shoulder maintenance that can be incorporated in daily training activities of the athletes in order to decrease the occurrence of injuries. Three part training program was designed consisting of specific warm up, strengthening and stabilization exercises and stretching exercises. The aim of the specific warm up was to prepare the shoulder for the training loads, mimicking the overhead movements and stimulating the stabilization in the joint. Strengthening and stabilization exercises aimed to strengthen external rotators in the shoulder and improve the stabilization of the shoulder joint by targeting specific muscles such as serratus anterior. The focus of stretching exercises was to stretch internal rotation muscles, which experience high loads in the overhead athlete's training. An effective training program that can be performed with minimal equipment and in a short time frame was designed to enable its simple incorporation into the daily training of overhead athletes.